2014
DOI: 10.5505/1304.7361.2014.58224
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Length of Stay of Patients in Emergency Department Observation Units at Teaching and Research Hospitals in Turkey

Abstract: SUMMARYObjectivesThis study aimed to determine the reasons for long stays in monitoring units and to propose a solution.MethodsThe patients who were followed in monitoring units of emergency service and the factors affecting the length of their hospital stay were analyzed retrospectively. Demographic features, their initial complaint that lead to monitoring, diagnosis, their means of arrival to emergency service, their admittance date and hour, medical history, basic vital signs, length of stay in emergency se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…This study reveals that lack of ICU bed (AOR = 0.022, 95% CI: (0.002,0.201)) has a significant association with delayed ICU admission and it shows that critically ill patients were less likely to transfer with less than 6 h by 97% when there is lack of ICU bed. This study was consistent with a study conducted in Turkey which shows, lack of space in the intensive care unit had a significant association for delayed ICU admission [ 12 ]. Furthermore, this study was supported with another study conducted in Ethiopia, which shows shortage of ICU beds were significant association with delayed ICU admission(AOR = 8.7, 95%CI:(3.2–23.2)) [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study reveals that lack of ICU bed (AOR = 0.022, 95% CI: (0.002,0.201)) has a significant association with delayed ICU admission and it shows that critically ill patients were less likely to transfer with less than 6 h by 97% when there is lack of ICU bed. This study was consistent with a study conducted in Turkey which shows, lack of space in the intensive care unit had a significant association for delayed ICU admission [ 12 ]. Furthermore, this study was supported with another study conducted in Ethiopia, which shows shortage of ICU beds were significant association with delayed ICU admission(AOR = 8.7, 95%CI:(3.2–23.2)) [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…In another study, patients aged 75 years or older constituted the largest proportion of the total study population (29.5%, n = 178), and 52.4% (n = 316) of the monitored patients were aged at least 65 years (Mahsanlar et al, 2014). The results of these studies indicated that geriatric patients constituted a major proportion of the patients who required monitored observation.…”
Section: Introductionmentioning
confidence: 89%
“…Studies of ED length of stay have identified both extrinsic and intrinsic factors. Two broad extrinsic factors, which are not under the control of the ED, have been identified (Jarvis, 2016): increased attendance/ departmental occupancy (Bergs et al, 2014) and bed availability or capacity in wards to which patients may be discharged (Mahsanlar et al, 2014). Intrinsic factors include patient characteristics, for example older patients (Hosseininejad et al, 2017), Ross, A. J., Murrells, T., Kirby, T., Jaye, P., & Anderson, J. E. (2019).…”
Section: Emergency Department Length Of Staymentioning
confidence: 99%